Effect of Sitting Baduanjin exercise on early rehabilitation of sepsis patients with non-invasive ventilation : a randomized controlled trial - Ming-Gui Chen; Fangfang Wang; Lixia Huang; Tingjie Qi; Hanhua Guo; Rui-Xiang Zeng; Xiaoyan Li; Haizhen Chen; Min-Zhou Zhang; Liheng Guo; Xiaoxuan Zhang (BMC, 2024)
Abstract Background For patients with sepsis receiving non-invasive ventilation (NIV), early rehabilitation is crucial. The Sitting Baduanjin (SBE) is an efficient early rehabilitation exercise suitable for bed patients. There is no consensus about the effect of SBE on the early rehabilitation of septic patients with NIV. This study focused on how the SBE affected the early rehabilitation of sepsis patients with NIV. Methods 96 sepsis patients with NIV were randomly assigned to either an Baduanjin group that received the SBE based on the routine rehabilitation exercise (n = 48) or a control group (n = 48) that received routine rehabilitation exercise. The primary outcome was the Medical Research Council(MRC)score, and the Barthel Index score, the duration of NIV, length of ICU stay, length of total stay, hospitalization expense as secondary outcomes. Results A total of 245 sepsis patients were screened, with 96 randomly assigned. The study was completed by 90 patients out of the 96 participants.Results revealed that the MRC score increased in both groups, but the improvement of muscle strength in Baduanjin group was more obvious, with statistical significance (p < 0.001).There was statistically significantly difference between the two groups in Barthel Index at the day of transfer out of ICU(P = 0.028).The patients in the Baduanjin group had an average reduction of 24.09 h in the duration of NIV and 3.35 days in total length of hospital stay compared with the control group (p < 0.05).Of note, the Baduanjin group had significantly reduction the total hospitalization expense. No serious adverse events occurred during the intervention period. Conclusions In patients with sepsis, the SBE appears to improve muscle strength and activities of daily living (ADL), and lowed the duration of NIV, the length of the total stay, and the hospitalization expense. Trial registration The study registered on the Chinese Clinical Trial Registry ( www.chictr.org.cn ), Clinical Trials identifier ChiCTR1800015011 (28/02/2018).